The Influence of Asset Growth, Asset Structure and Profitability on Company Value in Industrial Companies on The IDX - Melani Octavia; Adila Sari; Natasha Natasha; Seprint Purva; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
This study uses associative tests to analyze and obtain empirical evidence, whether asset growth, asset structure and profitability have a significant effect on the company's value. The data used is secondary data taken from the official website, namely www.idx.go.id. The results of this study showed that individually asset growth had a positive and significant effect on the company's value, then individually asset structure and profitability had a positive and insignificant effect on the company's value. However, simultaneously the three independent variables have a significant effect on the value of the company with an influence value of 15%, where the other 85% value is influenced by other variables that are not included by the researcher.